Optimizing Science Learning: A Journey into Developing Problem-Based Learning Animated Videos - Putu Arya Widiastawan; Basilius Redan Werang; Putu Rahayu Ujianti (International Journal of Natural Science and Engineering, 2023)
The minimal utilization of innovative and interactive teaching and learning media causes limited understanding of scientific and abstract concepts in science, as well as a decline in student learning achievement. This study aims to develop a problem-based learning animation video for science learning. This study includes 4D modelled development research which is composed of the stages of define, design, develop, and disseminate. The subjects were two subject content experts, two learning media experts, two learning design experts, one homeroom teacher, three students for individual test, and six students for small group test. Data collection using questionnaire. Instruments to collect data on subject content validity instruments, learning media validity instruments, learning design validity instruments. The techniques used in analysing data are qualitative descriptive analysis and quantitative descriptive analysis techniques. The media product validity test results obtained subject matter expert test results with an average overall of 3.77 (excellent). Learning media experts with an average overall of 3.63 (excellent). Learning design experts with an average overall of 3.83 (excellent). Teacher practitioner test results with an overall average of 3.96 (excellent), individual test results with an average overall of 3.80 (excellent) and small group test results of 3.78 (excellent). The conclusion can be drawn that the animated video of science learning based on problem-based learning is able to optimize the learning outcomes of grade III elementary school students.